2017
DOI: 10.1007/978-3-319-62416-7_27
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Knee Joints and Quantification of Knee Osteoarthritis Severity Using Convolutional Neural Networks

Abstract: Abstract. This paper introduces a new approach to automatically quantify the severity of knee OA using X-ray images. Automatically quantifying knee OA severity involves two steps: first, automatically localizing the knee joints; next, classifying the localized knee joint images. We introduce a new approach to automatically detect the knee joints using a fully convolutional neural network (FCN). We train convolutional neural networks (CNN) from scratch to automatically quantify the knee OA severity optimizing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 18 publications
2
115
1
2
Order By: Relevance
“…We have demonstrated that statistical models, using patients' questionnaire data, could predict KOA severity level with a good level of accuracy (RMSE: 0.974 & 0.943). The prediction performance of the statistical models presented in this paper are comparable to models using X-ray image data based on model performance as assessed by RMSE measures [26][27][28] . In particular we have demonstrated that functional impairment at severity levels 1 and 2 can be predicted by our statistical models (Elastic Net & Random Forest and LMM) trained from the patients' assessment data to a level of accuracy similar to the accuracy achieved on the basis of CNN model trained on X-ray images.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…We have demonstrated that statistical models, using patients' questionnaire data, could predict KOA severity level with a good level of accuracy (RMSE: 0.974 & 0.943). The prediction performance of the statistical models presented in this paper are comparable to models using X-ray image data based on model performance as assessed by RMSE measures [26][27][28] . In particular we have demonstrated that functional impairment at severity levels 1 and 2 can be predicted by our statistical models (Elastic Net & Random Forest and LMM) trained from the patients' assessment data to a level of accuracy similar to the accuracy achieved on the basis of CNN model trained on X-ray images.…”
Section: Discussionmentioning
confidence: 91%
“…To train and validate the predictive models we used a training and validation data split as shown in Table 1 (roughly a 70% -30% split). To make valid comparisons, we used the same validation set in the models developed on patient's questionnaire data and the model developed using X-ray images 26,27 . The validation set contained data for both knees for 846 patients, i.e.…”
Section: Exploratory Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we extend the approach by employing deep convolutional neural networks (CNNs). [29][30][31] Originally, CNNs were developed for image recognition task, 31,32 but recently, CNNs are also been applied to several medical applications, for example, diagnostic chest X-Rays, 33,34 fracture detection, [35][36][37] mammography, 38 low-dose X-ray tomography, [39][40][41] detection of osteoarthritis, 42,43 diagnosis of retinal diseases, 44 Alzheimer's disease diagnostics, [45][46][47] and MRI segmentation. 48 CNNs are also applied to the risk stratification of hypertension from PPG waveform data.…”
Section: Introductionmentioning
confidence: 99%